If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7z + -1z = -1 + 3z + -1 + -1 Combine like terms: 7z + -1z = 6z 6z = -1 + 3z + -1 + -1 Reorder the terms: 6z = -1 + -1 + -1 + 3z Combine like terms: -1 + -1 = -2 6z = -2 + -1 + 3z Combine like terms: -2 + -1 = -3 6z = -3 + 3z Solving 6z = -3 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. 6z + -3z = -3 + 3z + -3z Combine like terms: 6z + -3z = 3z 3z = -3 + 3z + -3z Combine like terms: 3z + -3z = 0 3z = -3 + 0 3z = -3 Divide each side by '3'. z = -1 Simplifying z = -1
| 4x+3=6+2x+25 | | 4x^2+4x-5=2x(x+3)-1 | | 1.52g-11=0.40 | | -2-2x=6x-50 | | 0.24p+1.17=1.8 | | 45+90x=585 | | 9x+8y=13.83 | | -5r-5r=4-8r-4r | | 48750-75+175=50750-150 | | 0.24p+1.17=1.29 | | -2x-6=2(2x-3) | | x=6.9375+-0.4375y | | -9=3(-c+2) | | 1X+4X=58 | | -20(y+2)+6(4y-4)=3(y-6)+12 | | -0.24p+1.602=1.8 | | 12x-3=4x | | 3(x-2)-4=4x-2 | | 9y=2y+35 | | v^2-2=65 | | 2y+1=23 | | 12k-32=24 | | -n+1-7n=9-7n | | -3+6x=x+7 | | z+3.6=2.5 | | -0.24p+1.602=1.29 | | 1X+4Y=58 | | -5x-10=-3+2x | | 7(n-4)-(6-3n)=9n | | 0,001*0,001x=1/8 | | 2+3x=-5x-6 | | 2x-5=-2+x |